(untitled) (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2025)
This article examines the issue of joint property distribution for widows whose husbands have passed away in Acehnese society. The problem arises due to tensions between national law, Islamic law, and local customary practices. In many cases, the wife receives no share of the jointly acquired assets, as they are treated solely as inheritance to be distributed among the heirs. This study employs a normative juridical approach by conducting a literature review of previous studies, statutory regulations (Marriage Law, Compilation of Islamic Law, Aceh Qanun), and case studies. The findings reveal a disconnection between formal legal norms and local practices, where asset distribution often follows customary methods without considering the wife’s legal rights under Indonesian law. The concept of joint property is not yet fully understood or implemented in Aceh, where patriarchal family structures and the dominance of the husband’s relatives prevail. Therefore, legal harmonization and stronger institutional roles—such as those of the Sharia Court and the Office of Religious Affairs (KUA)—are needed to ensure justice and legal protection for widows. Moreover, legal education for the public is essential to enhance awareness of women’s rights in the distribution of joint property following a husband’s death.